Analisis Dampak Influencer Marketing dan Customer Review Terhadap Impulse Buying dengan Price Discount sebagai Variabel Moderasi Pada Platform Tiktok Shop - Vania, Amelindha; Salsabila, Kamaludin Ahmad (Universitas Batanghari Jambi, 2025)
This study aims to analyze the impact of Influencer Marketing and Customer Reviews on Impulse Buying among university students in Malang, with Price Discount as a moderating variable on the TikTok Shop platform. Data were collected through a survey of 152 respondents using purposive sampling, and analyzed using multiple linear regression. The results show that both Influencer Marketing and Customer Reviews have a positive and significant effect on Impulse Buying, with Customer Reviews having a greater impact compared to Influencer Marketing. Additionally, Price Discount was found to have a significant effect on Impulse Buying and moderates the relationship between Influencer Marketing and Impulse Buying. However, the interaction between Customer Reviews and Price Discount showed a negative impact on Impulse Buying, indicating that price discounts are more dominant than customer reviews. These findings confirm that social factors and pricing play a crucial role in driving impulse buying on social media-based e-commerce platforms. This research provides insights for marketers to design strategies that integrate influencer promotions, customer reviews, and price discounts to increase impulse buying among young consumers.